De volta à corrente da vida : vivência receptiva e vida cotidiana na Estética de György Lukács - Carolina de Paula Peters (2023)
This research was dedicated to the relationship between receptive aesthetic experience and everyday life in the late thought of György Lukács (1885-1971), particularly as it figures in his book The Peculiarity of the Aesthetic, from 1963. Its main objective was to delineate, within the categorical complex of this work, the author’s conceiving on the confluence between art and everyday life regarding the reception of works of art, also pointing out their possible repercussions on other spheres of the social being, notably the reverberation of the aesthetic on ethical behavior, but also delimiting the relationships between art and politics. Through immanent reading, we sought to recognize in Lukacsian textuality the main theoretical motives of this formulation, which articulates the “enclosed world” of works of art to questions of a practical nature, typical of everyday life: the generalization of the Aristotelian category of catharsis, operated by the Hungarian Marxist; the characterization of art’s defetishizing mission; the problem of (in)determination in aesthetic objectivity; the becoming ganze Mensch of der Mensch ganz as distinguishing between the receiving subject and everyday life’s subjectivity; finally his considerations on before and after the receptive experience. Preliminarily, this thesis carries out a literature review, highlighting those scholars who anyhow contributed to the issue; then it presents a brief biographical-bibliographic sketch, which seeks to place the project of his great Aesthetics in the course of Lukács’ intellectual itinerary and, subsequently, within it, the discussion about the social function of art, in general, and, more specifically, on the aesthetic effect, and receptive experience, object to this investigation. Based on the assumption of subject-object identity in the aesthetic realm, in exposing the analysis of categories, it was decided to reasonably abstract those constellations concerning the subjective dimension of receptive experiences from those relating to the objectivity of the evocative character of authentic works of art – both inseparable in receptive activity, but for the purposes of proper theoretical understanding only, relative and circumstantially isolated.